Ruptura prematura de membranas en paciente de 23 semanas de gestación. - Acosta Moncada, Martha Juleisi (2020)
Premature ruptura of membranes is defined as the loss of integrity of the ovular membranes that occurs from 20 weeks of gestation until before the onset of labor, causing increased maternal-fetal morbidity and mortality. The present case study was developed with the objective of knowing the diagnosis of premature ruptura of membranes in a pregnant woman of 23 weeks of gestation studies have reported that it can be due to biochemical, physiological, pathological and environmental factos. Thanks to the expectant management of recent years, it has been posible to reduce the risk factor sor various complications that can occur due to this pathology, achieving as a result a full-term pregnancy without any complications. The purpose of carrying out this case stady is to contribute to the knowledge that women should have from the momento of conception to the end of their pregnancy to protect intrauterine life.